171k views
4 votes
Drag each expression to show whether it is equivalent to

-1.3x - (-8.9x), -1.3 + (-8.9X) or nethier

−1.3x−8.9x

8.9x+(−1.3x)

−8.9x+(−1.3x)

8.9x−(−1.3x)

−1.3x+8.9x

−8.9x+1.3x


3 Boxes showing witch one is going.

−1.3x−(−8.9x)

−1.3x+(−8.9x)

Neither

User Starbolin
by
5.6k points

2 Answers

2 votes

Answer:

Take a look yourself

Explanation:

Equivalent expressions are expressions which are equal. This means they simplify to the same expression. Simplify the two expressions -1.3x - (-8.9x) = 7.6x and -1.3 + (-8.9X) = -10.2x.

Then simplify each option to determine if it is equal -1.3x - (-8.9x), -1.3 + (-8.9X) or neither:

−1.3x−8.9x = -10.2x. This is equivalent to -1.3 + (-8.9X) .

8.9x+(−1.3x) = 7.6x This is equivalent to -1.3x - (-8.9x) .

−8.9x+(−1.3x) = -10.2x This is equivalent to -1.3 + (-8.9X) .

8.9x−(−1.3x) = 10.2x Neither

−1.3x+8.9x = 7.6x This is equivalent to -1.3x - (-8.9x) .

−8.9x+1.3x = -7.6x Neither

User BobGao
by
5.4k points
1 vote

Answer:

See below.

Explanation:

Equivalent expressions are expressions which are equal. This means they simplify to the same expression. Simplify the two expressions -1.3x - (-8.9x) = 7.6x and -1.3 + (-8.9X) = -10.2x.

Then simplify each option to determine if it is equal -1.3x - (-8.9x), -1.3 + (-8.9X) or neither:

−1.3x−8.9x = -10.2x. This is equivalent to -1.3 + (-8.9X) .

8.9x+(−1.3x) = 7.6x This is equivalent to -1.3x - (-8.9x) .

−8.9x+(−1.3x) = -10.2x This is equivalent to -1.3 + (-8.9X) .

8.9x−(−1.3x) = 10.2x Neither

−1.3x+8.9x = 7.6x This is equivalent to -1.3x - (-8.9x) .

−8.9x+1.3x = -7.6x Neither

User HumeNi
by
5.5k points